Sustainability level of mangrove forest management based on RAP-MForest approach in Pancer Cengkrong, Trenggalek District, Indonesia - Agra Dewi Sabrina; Ramadhandi, Ananda Rilo; Alya Afra Inas Nur; Nor Liza; Sutarno; Yap, Chee Kong; Muhammad Indrawan; Setyawan, Ahmad Dwi (Smujo International, 2022)
Mangrove forest area is a coastal resource that benefits the community's welfare. Protection and preservation of the mangrove ecosystem need to be carried out by taking into account various aspects to achieve sustainability. This study aims to analyze the level of sustainability of mangrove forest management and the contributing factors in the Pancer Cengkrong Mangrove Forest area in Karanggandu Village, Trenggalek District, East Java, Indonesia. This research was conducted in June 2022 through field interviews and literature studies. Three dimensions (ecological, economic, and social) were selected, along with their attributes. Each attribute was scored to indicate the status of sustainability. Then, the data obtained were processed by Multi-Dimensional Scaling (MDS) analysis using the Rapid Appraisal for Mangrove Forest (RAP-MForest) method. Furthermore, leverage analysis determines the sensitive attributes in each dimension. The results depicted that management in Pancer Cengkrong Mangrove Forest is less sustainable in the economic dimension and fairly sustainable in the two remaining dimensions. The social dimension achieved the highest sustainability index value at 72.92. Furthermore, knowledge of the sustainability index and sensitive factors can help provide recommendations for management in the Pancer Cengkrong mangrove area to achieve a sustainable level. In this case, the economic dimension should be more concerned with promoting environmentally sustainable development.